Analisis Konsep dan Signifikansi Ijtihad Rasulullah Saw. Dalam Pembentukan Hukum Islam - Achmad Alfian Mujaddid; Fatmawati F (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
When the Prophet was still alive, the supremacy of law was based on two sources, namely Allah's revelation and the ijtihad of the Prophet Muhammad. An event that requires the existence of a law may arise from a question or dispute, even at the request of an apostle, Allah revealed to his apostles the verses of the Qur'an which explain the law that he wants to convey to his people. So this article will answer the status of the position of ijtihad during the time of the Prophet Muhammad based on the meaning and pattern of ijtihad. Using a descriptive-analytical approach, this literary study examines various situations of Muhammad as an ordinary human being and as a prophet and apostle in carrying out his daily mission. This type of library research is only based on published documents such as books, journals, and others. Normative research methods or library legal research are used as research methods. His position as a prophet and apostle of course makes his ijtihad more important than the ijtihad of Muslims in general. Therefore, ijtihad has its position in Islamic teachings.